The people's Zion : southern Africa, the United States, and a transatlantic faith-healing movement - Cabrita, Joel, 1980- (The Belknap Press of Harvard University Press, 2018)
Until now, the remarkable transatlantic story of Southern Africa's largest popular religious phenomenon has never been told. The People's Zion is the history of the Zionist movement: a vast federation of thousands of African churches which identifies itself with the original faith-healing 'Zionist' church founded in the American Midwest (unrelated to Jewish Zionism). The story starts when Zionists in Chicago - largely socially-marginalized northern European immigrants and African-Americans - founded a utopian community in 1900 called 'Zion City'. Rejecting the idea that medical professionals were uniquely equipped to deal with ill-health, residents embraced faith healing instead of bio-medicine. Zion City also became well-known as one of the first multi-racial religious communities in the USA. Circulated to South Africa via missionaries and the church's literature, the Zionist movement thrived amongst white and black workers drawn to the city of Johannesburg by the discovery of gold. In Johannesburg as in Chicago, these early devotees of faith healing hoped for a color-blind society.--